Hemophilic pseudotumor of the ankle: a case report - Rodríguez Ciodaro, Ricardo; Pardo Laverde, Carlos Eduardo; Guerrero Forero, Álvaro Santiago; Solano Trujillo, María Helena; Caicedo Donoso, Claudia; Hernández Arango, Nicolás (Journal of the Foot & Ankle, 2021)
Hemophilic pseudotumors are little prevalent lesions associated with coagulation factor VIII or IX deficiency that characterizes hemophilia. Their most frequent location are regions such as hips or iliopsoas, whereas distal joints are rare locations. In the present case, we reported the development of a hemophilic pseudotumor related to a conventional anterolateral ankle arthroscopy in a patient with mild hemophilia A who required surgical management for hemophilic arthropathy. Level of Evidence V; Therapeutic Studies; Expert Opinion.